Dzieje biblioteki Arystotelesa - Warda, Elwira (Archiwa, Biblioteki i Muzea Kościelne, 2011)
Reading in Hellas developed quite slowly in the first period of the book development. However, more and more people read and possessed books. History reveals that ancient Greeks possessed small book collections. One of them was Aristotle of Stagira who is considered to be the first real book collector. His library held 143 works in 400 books. Before his death, he bequeathed his whole book collection to Teofrast of Eresos. In the course of time the library “changed hands”. It even became the part of Sulla’s war loot and hence it was in Rome. The library in Alexandria also possessed a substantial part of Aristotle’s books. After the collapse of Greece, Aristotle’s writings were kept in Syria. In the 4th century in Mesopotamia and then Aristotle’s writings along with other Greek philosophers were read in Arabia. The expansion of his philosophy to the West was possible due to the expansion of the Mahomet’s followers to the Pyrenees Peninsula. Thanks to the Arab philosophers, Latin Europe became acquainted with Aristotle’s philosophical legacy. At the end of the 19th century Aristotle was the talk of the world of science due to the new archeological discoveries. Dry sands of the Egyptian desert preserved papyruses with the fragments of different ancient texts. And thus Aristotle’s “The Constitution of the Athenians” was discovered, the text whose title had been only known before this archeological find.